The Influence of Self-Confidence and Growth Mindset on Students’ Interest in Learning Economics: A Study of Grade XI Social Science Students at Senior High School - Muhammad Rifqi Farhan Hasibuan; Indra Maipita (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to examine the influence of self-confidence and growth mindset on the interest in learning Economics among Grade XI Social Science students at SMA Negeri 2 Percut Sei Tuan. A quantitative approach with a regression analysis design was employed. The sample consisted of 75 students selected through a total sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. The data were analyzed using multiple linear regression. The findings revealed that self-confidence had a positive and significant effect on students’ interest in learning Economics (t = 2.895, p = 0.005), indicating that higher levels of self-confidence were associated with greater learning interest. Similarly, growth mindset showed a positive and significant effect on learning interest (t = 2.885, p = 0.005), suggesting that students who believe their abilities can be developed tend to demonstrate stronger interest in learning Economics. Simultaneously, self-confidence and growth mindset significantly influenced students’ interest in learning Economics (F = 27.589, p 0.001). The coefficient of determination (R² = 0.434) indicated that 43.4% of the variance in students’ learning interest could be explained by these two variables, while the remaining 56.6% was influenced by other factors not examined in this study. The study concludes that self-confidence and growth mindset are important psychological factors that contribute to enhancing students’ interest in learning Economics. Therefore, educators and school administrators should implement learning strategies that foster students’ confidence and encourage the development of a growth mindset to promote greater engagement in learning.